THE ROLE OF QUICK SERVICE RESTAURANT ON CONSUMER PURCHASE INTENTION AND CROSS-CATEGORY BUYING IN MINIMARKET - Trisandy, Yudhi; Tjandrasa, Benny Budiawan; Suwarno, Henky Lisan (Graduate Program of Universitas Tarumanagara, 2025)
The development of minimarkets, which not only sell grocery needs but also provide ready-to-eat food and beverage products, has become a phenomenon that can be found in various major cities in Indonesia. This study aims to determine the relationship between purchase intention and cross-category buying, as well as the role of the service quality dimension of quick service restaurants for minimarket customers that provide both types of services in the store. Minimarket customers are known to have the intention to make purchases across categories, but it is still unknown whether the service quality dimension in the quick service restaurant service can strengthen the shopping intention to make purchases of both categories simultaneously. Through 155 respondents who are minimarket customers who provide two types of product categories in Denpasar Raya, and also data analysis using the Structural Equation Modeling (SEM) method, it is known that there is a strong influence of purchase intention on cross-category buying for minimarket customers. Therefore, the development of various types of services and products from different categories is possible for this business model. Another finding from this study states that the dimensions of quick service restaurant service quality do not strengthen the influence of shopping intentions on cross-category buying, especially for customers aged 21-35 years or those commonly known as the generation Z and millennial age groups.